Essence and Representation as Moments of Mediation in the Hegelian System: a Comparison between the Logic and the Psychology of the Subjective Spirit - Barnaba, Martina (Revista Eletrônica Estudos Hegelianos, 2021)
The aim of this contribution is to point out the parallelism between the three moments of the Hegelian Logic (Being, Essence and Concept) and the three moments of his Encyclopedia Psychology (intuition, representation and thought), focusing especially on the role of mediation enacted by the second moments, Essence and representation. In line with the general Hegelian assumption of the identity between logic and reality, the complex functioning of the movement of the Essence can be regarded, in fact, as the foundation of the movement of representation. Thanks to the same dual constitution they share, Essence and representation both offer a mediation within themselves and between their respective extremes: representation splits itself in itself and stands as a middle ground between the immediacy of intuition and the rational synthesis of thought; in a similar way Essence is characterized by constant internal oppositions and possesses both elements of Being and of Concept. The paper will therefore explore at first the doctrine of the Essence as reported in the Science of Logic. In this section three important aspects will be highlighted: the internalization movement of the Erinnerung, which appears in the transition from Being to Essence; the primary dynamic of the Essence in its specific working, that is reflection; and lastly the peculiar “median role” that Essence embodies in its linking of Being and Concept together. In the second part of the paper the form of representation in the psychology of the Subjective Spirit will be analyzed in order to retrace these same elements observed in the Logic and present them as representation’s own mechanism of mediation. The main focus will be the articulation of the section of imagination and phantasy, in which the element of the symbol is contained. In conclusion the circular character of the mediation inside the totality of the system will be briefly addressed alongside the importance of the negative moment of difference that Essence and representation enact in the development of the dialectics.